(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
The structure of the leaf epidermis surface of 22 species from section Medium DC. of genus Campanula L. in the flora of Ukraine is investigated for the first time using a scanning electron microscope. The common characters for all species (amphistomous type of leaf blade, evenly spaced, not immersed anisocyte stomata, a well-developed crinkled cuticle; awl- and sickleshaped, bearded and hoary downiness, the location of wax deposits - crusts and / or laminas; a common type of topography) and specific characters (relief type, peculiarities of hairness) are identified.